2005
DOI: 10.7202/706071ar
|View full text |Cite
|
Sign up to set email alerts
|

Principles of insecticide resistance management

Abstract: La demande pour des stratégies efficaces de gestion de la résistance se fait de plus en plus pressante, au fur et à mesure que le nombre d'espèces résistantes aux insecticides augmente mondialement alors que les ressources insecticides diminuent. Les perspectives de développement de telles stratégies sont accrues par les développements récents en biochimie, en génétique moléculaire, en écologie, en dynamique, en dépistage et dans d'autres aspects importants de la résistance. Les approches généralement reconnue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 41 publications
1
69
0
3
Order By: Relevance
“…Selection with insecticides in treated areas and constant migration from untreated regions could be thought of as a source-sink model where continuous susceptible migration could significantly delay the development of resistance in treated regions, and combined with the assumed fitness costs of resistance this could hinder or even prevent evolution of resistance even more efficiently, as shown by many management models and field studies (Argentine et al, 1994;Georghiou, 1994;Raymond and Marguine, 1994;Peck, 1997;Lenormand and Raymond, 1998;Lenormand, 2002;Tyutyunov et al, 2008). In this study, our results showed that in a resistant laboratory strain of Musca domestica with continuous susceptible migration, both the level of resistance and the load of fitness costs could be eroded efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection with insecticides in treated areas and constant migration from untreated regions could be thought of as a source-sink model where continuous susceptible migration could significantly delay the development of resistance in treated regions, and combined with the assumed fitness costs of resistance this could hinder or even prevent evolution of resistance even more efficiently, as shown by many management models and field studies (Argentine et al, 1994;Georghiou, 1994;Raymond and Marguine, 1994;Peck, 1997;Lenormand and Raymond, 1998;Lenormand, 2002;Tyutyunov et al, 2008). In this study, our results showed that in a resistant laboratory strain of Musca domestica with continuous susceptible migration, both the level of resistance and the load of fitness costs could be eroded efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The origins, spread, and mechanisms of insecticide resistance have importance in both theoretical and practical issues (Hemingway, 2000;ffrench-Constant et al, 2004). From the beginning of the first insecticide treatment programs against insect pests, many insect species developed significant resistance levels against insecticides, and the number of resistant populations is still increasing (Georghiou, 1994;Denholm et al, 2002;Hemingway et al, 2002;Hardstone and Scott, 2010). Resistance against pesticides is seen as the product of 2 interacting forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are hundreds of different insect pest species that are under chemical control, and each species represents several distinct combinations of biological and ecological characteristics. Management by moderation should be the basic approach and should be supplemented to the maximum possibly by integrated pest management measures (45). Interestingly, there are several different strategies that have been proposed to tackle the insecticide resistance crisis.…”
Section: Insecticide Resistance Management (Irm)mentioning
confidence: 99%
“…Among the types of resistance mechanisms, metabolism and action site insensitivity are the most important types. However, it is important to note that a reduction in the rate of cuticular penetration fosters both types of mechanisms in a more synergistic way (45,46). …”
Section: Three Principal Types Of Resistance Mechanismsmentioning
confidence: 99%